Increasing The Competitiveness Of Sukasari District UMKM Through Digital Technology-Based Cooperatives - Asep Dicky Supriatna; Franciskus Antonius Alijoyo (Jurnal Info Sains : Informatika dan Sains, 2023)
UMKM are a crucial driving force for economic growth in the national economy. However, many UMKM face challenges in accessing technology and broader markets. On the other hand, the digital era has brought about significant changes in the way businesses operate. In this context, digital cooperatives emerge as an innovative solution to overcome these barriers. This study aims to investigate how emerging UMKM can innovate and grow through the utilization of digital cooperatives. The results indicate that digital cooperatives can enhance visibility, market access, and technological innovation capacity for UMKM. Furthermore, collaboration between UMKM and digital cooperatives opens opportunities for scaling up businesses, expanding networks, and maximizing growth potential. With the right infrastructure and policy support, the integration of UMKM with digital cooperatives can serve as a catalyst for growth and innovation in this sector